Identification and distribution of nitric oxide synthase in the brain of adult Antarctic Teleosts - MASINI, MARIA ANGELA; STURLA, MADDALENA; F. RICCI; UVA, BIANCA MARIA (Springer Verlag Germany:Tiergartenstrasse 17, D 69121 Heidelberg Germany:011 49 6221 3450, EMAIL: g.braun@springer.de, INTERNET: http://www.springer.de, Fax: 011 49 6221 345229, 2005)
We investigated the presence of nitric oxide synthase (NOS) in brain of adult Antarctic teleosts by indirect immunofluorescence technique using a synthetic rat neuronal NOS (nNOS) antibody. The following species were examined: Trematomus bernacchii, Gymnodraco acuticeps, Histiodraco velifer, Cygnodraco mawsoni (haemoglobin-rich), Chionodraco hamatus and Pagetopsis macropterus (haemoglobin-free). Immunoreactive cell bodies were localized in dorsal telencephalon, in hypothalamus, in optic tectum of the mesencephalon as well as in Purkinje cells of the cerebellum. No differences were observed in the localization of the nNOS immunopositivity in the Antarctic teleosts brains examined and NOS distribution was similar to that described in other teleosts, suggesting that nitric oxide (NO) may also function as a neurotransmitter in the brain of Antarctic teleosts. A strong immunopositivity was observed in the cerebral blood vessels of the icefishes suggesting that NO may play a pivotal role in the regulation of the cerebral blood flow especially in these haemoglobin-free species.